The Effectiveness of the Antiinfamation Combination Gel of Okra Fruit (Abelmoschus esculentus) Extracts and Shallots Extract (Allium cepa L.) - Sara Nurmala; Moerfia Moerfia; Santi Novianti (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Wound is a condition that is the destruction of the unity or network components, which are specifically found the substance of tissue damaged or lost, either damage the continuity of the skin, mucous membranes and bones or other organs. Wound healing is a very complex process involving many cells. The process of wound healing is portrayed as occurs in biological surgical wound occurred. Several phases of wound healing are: the process of inflammation (inflammatory), the process of cell multiplication (proliferation) and cell maturation process (maturase). Okra is a plant that allegedly came from Southeast Asia. Okra has grown in many countries in almost all over the world. In the UK okra known as the Lady's Finger, in India it is called by the name of Bhindi while the United States called Gumbo. In Indonesia, this plant also has a local name that is Rabamea (Bima), Coffee Java (Java), Arabian Coffee (Sulawesi), Hoinu (Southeast Sulawesi), but better known by the name of okra. This study aims to determine the effective concentration and determine the length of time of wound healing using a combination gel okra fruit extract (Abelmoschus esculentus) And shallots (Allium cepa L.) as an anti-inflammatory against cuts in male white rats (Sprague -Dawley) with a length of observation for 9 days. This study uses Betadine® ointment as a positive control. The results showed the combination of fruit extract gel okra 6% and shallots 2% contained in the formula 3 most effective as an anti-inflammatory against cuts in male rats by administration for 6 days.